Coronary Artery Reimplantation and Berlin Heart EXCOR Rescue for Left Coronary Artery Atresia With Severe Ischemic Cardiomyopathy. Issue 6 (November 2021) - Wilkinson, Daniel; Lin, Yihan; Everett, Melanie; Auerbach, Scott; Morgan, Gareth; Mitchell, Max B.
We describe a successful bridge to recovery by coronary reimplantation and Berlin Heart EXCOR left ventricular assist device in a child with left main coronary artery ostial atresia and severe ischemic cardiomyopathy.